Rapidly progressive arthropathy identified on imaging of patients treated with Crizotinib for ALK-rearranged/ROS1-positive non small cell lung cancer: A retrospective single-center study - Yael Eshet; Liran Domachevsky; Noam Tau; Gregory Peters Founshtein; Michal Eifer; Jair Bar; Iris Eshed (PLoS ONE, 2026)
Objectives Progressive arthropathy was anecdotally described in patients exposed to crizotinib, a receptor tyrosine kinases inhibitor (TKI) used to treat anaplastic lymphoma kinase (ALK) or ROS Proto-Oncogene 1 (ROS1) positive non-small cell lung cancer (NSCLC). We aimed to evaluate the incidence of this adverse effect. Methods We retrospectively evaluated imaging studies of all patients in our institution receiving TKI for ALK-rearranged or ROS1-positive NSCLC (crizotinib, alectinib, lorlatinib, brigatinib). Results Between February 2012 and August 2023, out of a total number of 71 subjects (51% male, 36−88 years old) who received TKI’s for ALK-rearranged/ ROS1 positive NSCLC, 34/71 (47%) were exposed at least once to crizotinib treatment, while the other 37/71 (53%) patients received other TKI’s. Significantly higher incidence (p = 0.02) of irreversible, progressive arthropathy in one or more joints was detected in 18% (6/34, 95% CI: 0.1–0.26) of crizotinib-treated patients, up to 6 years after treatment initiation. Imaging findings included synovial proliferation and progressive arthropathy in hip and shoulder joints, and vertebral endplate destruction. Conclusion We found progressive arthropathy, mostly painless, in one or more joints or intervertebral spaces of patients receiving crizotinib for NSCLC.